2013
DOI: 10.1155/2013/415810
|View full text |Cite
|
Sign up to set email alerts
|

Cotrimoxazole-Induced Hypoglycaemia in a Patient with Churg-Strauss Syndrome

Abstract: Cotrimoxazole is a commonly used antimicrobial agent which is traditionally indicated in the management of pneumocystis infection of which HIV and immunosuppressed individuals are at high risk. Furthermore, it can be used on the long term for prophylactic indications. Hypoglycaemia following commencement of cotrimaoxazole is a rare adverse effect which was first described in 1988. We describe a case of hypoglycaemia shortly following initiation of cotrimoxazole indicated as long-term prophylaxis on a backgroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Interestingly, we present co-trimoxazole-induced hypoglycaemia despite a normal random cortisol and concomitant prescription of a corticosteroid (prednisolone), which in theory should be protective against this adverse effect owing to its promotion of insulin resistance 20. This phenomenon was also described by Senanayake et al ,20 who also report a reduction in serum glucose parallel to a reduction in steroid dosage, further suggesting the sulfonylurea-like effect of co-trimoxazole 2…”
Section: Discussionsupporting
confidence: 70%
“…Interestingly, we present co-trimoxazole-induced hypoglycaemia despite a normal random cortisol and concomitant prescription of a corticosteroid (prednisolone), which in theory should be protective against this adverse effect owing to its promotion of insulin resistance 20. This phenomenon was also described by Senanayake et al ,20 who also report a reduction in serum glucose parallel to a reduction in steroid dosage, further suggesting the sulfonylurea-like effect of co-trimoxazole 2…”
Section: Discussionsupporting
confidence: 70%
“…In this case, long-term steroid use was also a risk for prolonged hypoglycemia due to tertiary adrenal insufficiency, because steroids suppress the secretion of corticotropin-releasing hormone from the hypothalamus [30]. Senanayake et al reported a case of hypoglycemia caused by a prophylactic dose of TMP/SMX in a patient with eosinophilic granulomatosis with polyangiitis using prednisolone for immunosuppressive therapy, although the patient was without renal impairment [24]. Symptoms of hypoglycemia were ameliorated by increasing the prednisolone dosage.…”
Section: Discussionmentioning
confidence: 91%
“…The structural similarity of SMX with sulfonylurea may result in pancreatic insulin secretion, particularly at higher doses and in patients with renal impairment [6]. We reviewed previously reported 22 cases of TMP/ SMX-associated hypoglycemia [4,[6][7][8][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] (Table 2). In most of the cases (77%), patients had renal impairment (serum creatinine > 1.1 mg/dL and/or on renal replacement therapy).…”
Section: Discussionmentioning
confidence: 99%
“…6 This is because it is structurally similar to sulphonylureas, and it is thus thought to stimulate pancreatic beta-cell insulin secretion. 7 In fact, sulphonylureas were first created from the discovery of sulphonamide-induced hypoglycaemia in 1942. 6 Despite this link, hypoglycaemia is a surprisingly rare side effect of co-trimoxazole.…”
Section: Discussionmentioning
confidence: 99%